Knowledge, attitudes, and beliefs about HIV pre-exposure prophylaxis among US Air Force Health Care Providers. Issue 32 (August 2016) - Hakre, Shilpa; Blaylock, Jason M; Dawson, Peter; Beckett, Charmagne; Garges, Eric C; Michael, Nelson L; Danaher, Patrick J; Scott, Paul T; Okulicz, Jason F
Abstract : Abstract: Providers are central to effective implementation of HIV pre-exposure prophylaxis (PrEP). Primary care providers (PCP) and infectious disease physicians (ID) in the US Air Force (USAF) participated in a cross-sectional survey regarding knowledge, attitudes, and beliefs toward HIV PrEP. Characteristics associated with PrEP knowledge were assessed in univariate and multivariate analyses. Among 403 (40% of 1015 providers) participants, 9% (PCP 383, ID 20) ever prescribed PrEP. In univariate analysis, years in practice, number of HIV-infected patients treated in the past 12 months, past prescription of antiretrovirals for HIV prevention, frequency of prescribing PrEP in the past 12 months, and ever being questioned by a patient about PrEP were associated with PrEP knowledge ( P  < 0.05). In multivariate analysis, providers who had ever prescribed antiretrovirals to prevent HIV (AOR: 2.37, 95% CI: 1.27–4.42) had greater odds of high PrEP knowledge. Despite concerns about medication side effects (overall 67%: PCP 68%, ID 85%) and prescribing PrEP without clear evidence (overall 60%: PCP 65%, ID 62%), 64% (PCP 65%, ID 85%) of participants indicated PrEP should be offered in the Military Health System and 68% (PCP 70%, ID 100%) disagreed with the statement that their patient population was not at risk for HIV infection. Successful PrEP implementation in the USAF will require continued education and training of primary care providers to improve knowledge and mitigate concerns about PrEP. Abstract : Supplemental Digital Content is available in the text